1167. Trends in Multi-Drug-Resistant Gonorrhea, Gonococcal Isolate Surveillance Project, United States, 1987–2016. (26th November 2018) - St. Cyr, Sancta; Kersh, Ellen; Weinstock, Hillard; Torrone, Elizabeth
Abstract: Background: Neisseria gonorrhoeae's ability to develop resistance to antibiotics used for treatment and a limited development of new therapies have made this organism one of three urgent threat pathogens in the United States. We provide the first report of US trends in multi-drug-resistant (MDR) and extensively-drug-resistant (XDR) gonorrhea. Methods: The Gonococcal Isolate Surveillance Project (GISP) monitors trends in antimicrobial susceptibility in N. gonorrhoeae in the United States. Antimicrobial susceptibility testing by agar dilution is performed on urethral isolates from male patients at participating STD clinics. Minimum inhibitory concentration (MIC) are used to identify isolates with resistance or reduced susceptibility using the following criteria: fluoroquinolones (ciprofloxacin [MIC ≥1.0 μg/mL]) and elevated MICs to cephalosporins (cefixime [MIC ≥0.25 μg/mL], ceftriaxone [MIC ≥0.25 μg/mL]) and macrolides (azithromycin [MIC ≥1.0 μg/mL before 2005 and ≥2.0 μg/mL 2005–2016]). In this analysis, MDR is defined as resistance or elevated MICs to ≥2 classes of antimicrobials; XDR as resistance or elevated MICs to ≥3 classes. This classification excludes penicillin and tetracycline due to their long history and high prevalence of gonococcal resistance. Results: During 1987–2016, 159, 445 isolates were collected through GISP. In 1998, the first MDR strains were identified. Although only 0.04% of isolates that year, these isolates showed elevated MICs to both cephalosporins and macrolides. By 2010, 1.0% of GISP isolates were MDR with elevated MICs or resistance to two of the cephalosporins, macrolides, or fluoroquinolones. In 2011, the proportion of isolates that were MDR peaked at 1.3%. In 2016, after minor fluctuations, 1.1% of GISP isolates were considered MDR. Only one occurrence of XDR, in 2011, has been seen in GISP. The strain was resistant to fluoroquinolones with elevated MICs to both cephalosporins and macrolides. Conclusion: MDR and XDR gonorrhea have remained low over the past three decades; however, dual treatment with cephalosporins and macrolides is the last remaining recommended therapy for N. gonorrhoeae . Until new treatment options become available, a combination of surveillance and ensuring appropriate treatment are needed to delay further resistance. Disclosures: All authors: No reported disclosures.